Copper removal using Ochrobactrum species isolated from contaminated wastewater - Mustapha, Mohammed Umar; Halimoon, Normala; Wan Johari, Wan Lutfi (Department of Biology, Faculty of Science, Universiti Putra Malaysia, 2016)
Bacterial metal removal has received considerable attention recently, due to the potential use of microorganisms for treatment of contaminated wastewater. Removal and recovery of heavy metal ions from polluted wastewaters has appeared to be the potential alternative method for conventional treatment of contaminated wastewater. The purpose of the present work was to study the removal capacity of toxic metal from contaminated wastewater by using Ochrobactrum sp. isolated from contaminated wastewater using different pH and temperature. Bacteria species have a high surface area to volume ratio, due to their small size and thus, they can offer a large contact interface that would interact with metals ion. The interactions between metal ions and functional groups on the cell wall of the biomass were observed using SEM and EDX analysis. The results indicated that bacterial isolate Ochrobactrum sp. is a suitable biosorbent for the removal of Cu(II) ion from metal polluted wastewater and might be applicable to the development of possibly cheap biosorbent for removing and recovering copper from effluents.